Comparison of robotic magnetic navigation-guided and manual catheter ablation of ventricular arrhythmias arising from the papillary muscles. (1st May 2018) - Bassil, Guillaume; Liu, Christopher F; Markowitz, Steven M; Thomas, George; Ip, James E; Macatangay, Constancia; Maglione, Theodore; Saleh, Layth; Lerman, Bruce B; Cheung, Jim W
Abstract: Aims: Due to the complex anatomy of the left ventricular (LV) and right ventricular (RV) papillary muscles (PMs), PM ventricular arrhythmias (VAs) can be challenging to target with ablation. We sought to compare the outcomes of robotic magnetic navigation-guided (RMN) ablation and manual ablation of VAs arising from the LV and RV PMs. Methods and results: We evaluated 35 consecutive patients (mean age 65 ± 12 years, 69% male) who underwent catheter ablation of 38 VAs originating from the LV and RV PMs as confirmed by intracardiac echocardiography. Catheter ablation was initially performed using RMN-guidance in 24 (69%) patients and manual guidance in 11 (31%) patients. Demographic and procedural data were recorded and compared between the two groups. The VA sites of origin were mapped to 20 (53%) anterolateral LV PMs, 14 (37%) posteromedial LV PMs, and 4 (11%) RV PMs Acute successful ablation was achieved for 20 (74%) VAs using RMN-guided ablation and 8 (73%) VAs using manual ablation ( P = 1.000). Fluoroscopy times were significantly lower among patients undergoing RMN ablation compared to patients undergoing manual ablation [median 7.3, interquartile range (IQR) 3.9–18 vs. 24 (16–44) min; P = 0.005]. Retrograde transaortic approach was used in 1 (4%) RMN patients and 5 (46%) manual patients ( P = 0.005). No procedural complications were seen in study patients. Conclusion: Use of an RMN-guided approach to target PM VAs results in comparable success rates seen with manual ablation but with lower fluoroscopy times and decreased use of transaortic retrograde access.